Analysis of groundwater ion abnormality and its cause of centralized drinking water sources in Jieshou City, China - Su, Guifen; Liu, Guijian; Li, Yongli; Wang, Guanyu (Frontiers in Environmental Science, 2023)
Groundwater provides drinking water to city and rural residents; which is also one of the chief water sources for commercial and agricultural activities in Jieshou City. We collected and analyzed the samples of 18 underground water source wells in Jieshou. We investigated whether the water was of acceptable quality and had characteristics that exceeded the standard. This study was conducted to determine the chemical characteristics of groundwater and abnormally high super-standard ions found in groundwater. The hydrogeological conditions of the study area were analyzed through data collection; through sample collection and sample testing, the characteristics and types of water chemistry were analyzed by means of mathematical statistics analysis and the Piper chart. The genesis of water chemistry was discussed using the Gibbs chart and correlation analysis; the proportional coefficient of ion molar concentration was used to judge the source, origin, and forming process of groundwater chemical composition. The results show that the groundwater is classified as marginally alkaline water, with a composition of Na-HCO3. The cations are mainly Na+, and the anions are mainly HCO3−. According to the Ⅲ water standard of groundwater quality standard and comparing the content of each ion, Na+ and F− are the primary abnormal super-standard ions, and ions and compounds are the main occurrence states. The concentrations of Na+ and F− exceed the standard for class Ⅲ water. There was a positive correlation between the abnormal Na+ and F−, and the concentration of F− increased with the increase in monitoring depth. The causes of abnormal ions were mainly determined by the lithology of the aquifer in the study area, and most of them are fluorine-containing rocks, which are transferred into groundwater through leaching or hydration. The enrichment of Na+ and F− is influenced by the local primary geological setting, hydrochemical type, hydrogeological conditions, pH and artificial activities, and the primary geological setting is the main influencing factor.